2013
DOI: 10.1002/bin.1369
|View full text |Cite
|
Sign up to set email alerts
|

Parent Education Intervention Results in Decreased Challenging Behavior and Improved Task Engagement for Students With Disabilities During Academic Tasks

Abstract: Children with developmental disabilities and attention deficit hyperactivity disorder often engage in challenging behavior when presented with academic demands. Parents of school-age children with such diagnoses are commonly asked to assist their child with academic tasks but may struggle to do so as a result of challenging behavior. This study evaluated the effects of a parent education intervention on the challenging behaviors and task engagement of three school-age children with disabilities during academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Parents have informed intervention by completing functional behavior assessment (FBA) rating scales and interviews (e.g., Marcus, Swanson, & Vollmer, ) and conducting experimental functional analyses (e.g., Kurtz et al, ). Parents have also collaborated with professionals to develop a behavior intervention plan (BIP) (e.g., Buschbacher, Fox, & Clarke, ) and more broadly have participated in parent education and coaching programs to learn how to implement behavioral intervention strategies at home (Kuhn, Lerman, & Vorndran, ; Lerman, Swiezy, Perkins‐Parks, & Roane, ; Lequia, Machalicek, & Lyons, ; Marcus et al, ). Family members who learn to implement behavior support strategies benefit from decreased child challenging behavior and may experience reduced stress and depression in the process (Feldman & Werner, ; Koegel, Bimbela, & Schreibman, ; McConachie & Diggle, ; Schreibman, Kaneko, & Koegel, ; Vaughn, White, Johnston, & Dunlap, ).…”
mentioning
confidence: 99%
“…Parents have informed intervention by completing functional behavior assessment (FBA) rating scales and interviews (e.g., Marcus, Swanson, & Vollmer, ) and conducting experimental functional analyses (e.g., Kurtz et al, ). Parents have also collaborated with professionals to develop a behavior intervention plan (BIP) (e.g., Buschbacher, Fox, & Clarke, ) and more broadly have participated in parent education and coaching programs to learn how to implement behavioral intervention strategies at home (Kuhn, Lerman, & Vorndran, ; Lerman, Swiezy, Perkins‐Parks, & Roane, ; Lequia, Machalicek, & Lyons, ; Marcus et al, ). Family members who learn to implement behavior support strategies benefit from decreased child challenging behavior and may experience reduced stress and depression in the process (Feldman & Werner, ; Koegel, Bimbela, & Schreibman, ; McConachie & Diggle, ; Schreibman, Kaneko, & Koegel, ; Vaughn, White, Johnston, & Dunlap, ).…”
mentioning
confidence: 99%
“…In addition, highly preferred activities (e.g., computer access, video games, outside play) can present strong competition for student attention. Parents are also challenged in the home by a variety of demands (e.g., answering the phone, attending to the needs of other children, completing household tasks; Lequia et al, 2013). These issues make it even more important that homework assignments be made after an initial collaborative planning process.…”
Section: Discussionmentioning
confidence: 99%
“…For students with mild disabilities, determining the specific ways in which homework might enhance student skills and success is a critical first step. For many studentsespecially those with intellectual, learning, or behavioral issueshomework may be especially important in providing the extra time required for any newly taught skills to become established (e.g., Lequia, Machalicek, & Lyons, 2013). 534615T CXXXX10.1177/0040059914534615Council for Exceptional ChildrenTeaching Exceptional Children…”
Section: What Is the Appropriate Role Of Homework?mentioning
confidence: 99%
“…Family trainings were organized for mothers to help them become competent in implementing the program. Previous studies on family education showed that education programs for families were carried out through informative presentations, modeling, role play and feedback (Lequia et al, 2013;Mazurik-Charles & Stefanou, 2010). Training activities for mothers were carried out before the implementation process started.…”
Section: Methodsmentioning
confidence: 99%